Nitric oxide modulates interleukin-2-induced proliferation in CTLL-2 cells - J. Padrón; L. Glaría; O. Martinez; M. Torres; E. Lopez; R. Delgado; L. Caveda; A. Rojas (Mediators of Inflammation)
The role of the L-arginine–nitric oxide metabolic pathway was explored for interleukin-2-induced proliferation in the cytotoxic T lymphocyte clone CTLL-2. Specific inhibition of nitric oxide synthase significantly diminished, in a concentration-dependent manner, 3H-thymidine uptake of CTLL-2 cells in response to different concentrations of interleukin 2. Withdrawal of L-arginine from culture medium resulted as potent as the higher inhibition obtained when blocking nitric oxide synthase with L-arginine analogues. Furthermore, intermedial concentrations of Larginine and exogenous nitric oxide donors were found for achieving optimal IL2-induced proliferation of CTLL-2. These findings prompted us to suggest that intra- and/or inter-cellular nitric oxide signalling may contribute to the modulation of the IL2 mitogenic effect upon cytotoxic T lymphocytes.